The History and Development of Islamic Organizations in Banyumas:Muhammadiyah and Nahdlatul Ulama - Mohammad Nur Zamzam; Celline Afelindia Azzahra; Iis Nur Baiti; Shindi Aulia Agustina (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the history and development of Islamic organizations in Banyumas, Central Java, with particular focus on Muhammadiyah and Nahdlatul Ulama (NU) from the colonial period to the contemporary era. The research aims to analyze the historical foundations, organizational transformation, and socio-religious contributions of these organizations in shaping local Islamic dynamics. This study employs a qualitative descriptive approach integrating historical and sociological perspectives. Data were collected through literature review, document analysis, organizational archives, and interviews with local religious leaders and organizational figures. The findings reveal that the emergence of Muhammadiyah and NU in Banyumas was closely linked to the region’s Islamization process and the evolving socio-religious landscape of the early twentieth century. Over time, both organizations developed distinct institutional characteristics while maintaining significant influence in education, religious outreach, social welfare, and community empowerment. Their sustained presence demonstrates a strong capacity to adapt to changing social, political, and cultural conditions. The study concludes that Muhammadiyah and NU function not only as religious institutions but also as important actors in the construction of Islamic civil society and local social transformation in Banyumas.